2002
DOI: 10.1002/1521-3951(200201)229:1<433::aid-pssb433>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Confined Optical Vibrations in CdTe Quantum Dots and Clusters

Abstract: Absorption of far-infrared (FIR) radiation and Raman scattering in CdTe nano-crystals (spherical quantum dots (QDs) of several nanometers in size) and Cd 54 Te 32 (SCH 2 CH 2 OH) 8À 32 clusters prepared by colloidal synthesis were studied. Raman spectra of both QDs and clusters are dominated by a peak situated slightly below the bulk CdTe LO phonon frequency. Experimental FIR transmittance spectra of films containing CdTe clusters show a broad band between the bulk TO and LO phonon frequencies, while there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 15 publications
(25 reference statements)
4
14
0
1
Order By: Relevance
“…q % 150:0 cm À1 , which plays the role of the Fr€ ohlich mode [47]. The phonon mode for the present CdTe powder is centered at about 152.3 cm À1 , which is close to the Fr€ ohlich mode frequency, as seen in Fig.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…q % 150:0 cm À1 , which plays the role of the Fr€ ohlich mode [47]. The phonon mode for the present CdTe powder is centered at about 152.3 cm À1 , which is close to the Fr€ ohlich mode frequency, as seen in Fig.…”
Section: Discussionsupporting
confidence: 72%
“…, the X‐critical‐point LO‐phonon wave numbers of CdTe bulk are 4.03, 4.86, and 4.92 THz, which equals 134.3, 162.0, and 164.0 cm −1 , respectively. The resultant of the 134.3 and 164.0 cm −1 wave numbers gives a single peak centered at a wave number of ω0=true(ω12+ω32true)/2150.0 cm1, which plays the role of the Fröhlich mode . The phonon mode for the present CdTe powder is centered at about 152.3 cm −1 , which is close to the Fröhlich mode frequency, as seen in Fig.…”
Section: Discussionsupporting
confidence: 63%
“…33, we assume that the expression in square brackets in Eqn (22) can be approximated by [. 33, we assume that the expression in square brackets in Eqn (22) can be approximated by [.…”
Section: Kek H K F E Ke E R E F H K H E R H J Ij I 19mentioning
confidence: 99%
“…From the viewpoint of the model based on bulk dispersion curves, the strong spatial confinement along with lattice distortion due to the reconstruction induced by a domination of surface atoms can lead to the situation when only phonons (TO and LO) close to (bulk) zone boundary exist in NCs. These ZE phonons manifest themselves in Raman spectrum as a single broad feature because of a very small TO-LO splitting near International Journal of Spectroscopy 5 the zone boundary, as has been inferred previously for the description of IR phonon spectra of Cd 56 Te 32 clusters [43].In conclusion, the resonant Raman spectra of several kinds of II-VI NCs have been analyzed. It is shown that similar set of phonon modes can be derived from fitting the spectra of high enough quality.…”
mentioning
confidence: 99%